Proximate and Mineral Evaluation of Dried Composites of selected Leafy Vegetables - Achimugu, Solomon; Okolo, Judith C.; Obaje , Grace (Indonesian Food Science and Technology Journal, 2021)
This study aimed at determining the chemical qualities of six selected green leafy vegetables (pumpkin, moringa, chaya, A. spinach, scent leaf and cocoyam). Proximate result showed that the composite sample was significantly higher in all parameters except for carbohydrate where it was significantly least. Mineral analysis result ranged between 8.24-1315.8; 243.7-536.3; 23.61-35.92; 1.21-29.91 for Ca, Mg, Fe and Zn respectively. The quantity recorded for the composite sample is adequate enough to furnish for the daily requirement.